Legal Politics Systematizing Regional Head Election Campaigns in the Era of The Covid-19 Pandemic - Ari Sadewa; Rusliyanto Rusliyanto; Dewi Erowati (LPPM Universitas PGRI Sumatera Barat, 2021)
This study aims to analyze the legal politics of regulating the implementation of regional head election campaigns during the Covid-19 pandemic, and the factors that influence the regulation of regional head election campaigns during the Covid-19 pandemic. The theory used in this study is the theory of the electoral administration model and the theory of legal politics. The approach used in this study is a qualitative approach with library research, which uses normative legal research methods. The results of this study, the legal politics of regulating regional head election campaigns during the Covid-19 pandemic was influenced by: First, violations of health protocols that occurred during candidate registration, involving a large number of masses, resulting in crowds. Second, the increase in the number of Covid-19 cases, which has also begun to target election organizers and regional election participants. Third, the insistence of various parties to postpone the simultaneous 2020 regional head elections. Fourth, the agreement of the DPR RI through Commission II with the Government through the Ministry of Home Affairs and Election Organizers (KPU, Bawaslu, DKPP) in a Hearing Meeting (RDP) on September 21, 2020.